SUSTAINABILITY OF THE WATER REQUIREMENT OF TWO CULTIVARS OF OKRA UNDER THE USE OF COVER CROP AND MINIMUM TILLAGE SYSTEM - Alaa Salih Ati,; Shaima Sami Dawod,; Kasem Mosa Madlol AL-Halfi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
An experiment was carried out at one of the fields located south of Baghdad during the 2024 agricultural season to study the water requirements of two cultivars of okra, a local cultivar (Batra) and an Egyptian cultivar (Lahloba) under the effect of the previous crop compared with the absence of residues. The factorial experiment included the crop cultivar and the presence or absence of previous crop residues. The characteristics studied for these two factors and their interactions were the water requirement of the okra crop, water productivity, germination speed, plant height, number of leaves, and fresh pod yield. The presence of crop residues led to a decrease in water consumption by the crop (mm) and consequently a decrease in the amount of water used (m3) per hectare by 19.26% and an increase in both water productivity by 64.15%, the germination by about 7.3%, plant height (cm) by 22.7%, and the number of leaves per plant 13.6%, and the yield of fresh pods (kg/ha) is approximately 32.5%. The Egyptian cultivar (Lahloba) exceeded the local cultivar Batra in achieving the lowest water consumption and therefore the least amount of water used by 4.5% and the highest percentage of water productivity (10.5%), germination speed (7.3%), number of leaves per plant (4.2%) and fresh pod yield (kg/ ha) (5.9%), while the local cultivar Batra exceeded in achieving the highest average plant height reaching 143 cm compared to the average height of the Lahloba plant (142 cm), with an increase of 0.7%.